Comparative study of friction between metallic and conventional interactive self-ligating brackets in different alignment conditions - Sérgio Ricardo Jakob; Davison Matheus; Maria Cristina Jimenez-Pellegrin; Cecília Pedroso Turssi; Flávia Lucisano Botelho do Amaral (Dental Press Editora, 2014)
OBJECTIVE: The aim of this study was to compare the friction between three bracket models: conventional stainless steel (Ovation, Dentsply GAC), self-ligating ceramic (In-Ovation, Denstply GAC) and self-ligating stainless steel brackets (In-Ovation R, Dentsply GAC). METHODS: Five brackets were used for each model. They were bonded to an aluminum prototype that allowed the simulation of four misalignment situations (n = 10). Three of these situations occurred at the initial phase (in which a 0.016-in nickel-titanium wire was used): 1. horizontal; 2. vertical; and 3. simultaneous horizontal/vertical. One of the situations occurred at the final treatment phase: 4. no misalignment (in which a 0.019 x 0.025-inch stainless steel rectangular wire was used). The wires slipped through the brackets and friction was measured by a Universal Testing Machine. RESULTS: Analysis of variance followed by Tukey's Test for multiple comparisons (α = 0.05) were applied to assess the results. Significant interaction (p < 0.01) among groups was found. For the tests that simulated initial alignment, Ovation(r) bracket produced the highest friction. The two self-ligating models resulted in lower and similar values, except for the horizontal situation, in which In-Ovation C(r) showed lower friction, which was similar to the In-Ovation R(r) metallic model. For the no misalignment situation, the same results were observed. CONCLUSION: The self-ligating system was superior to the conventional one due to producing less friction. With regard to the material used for manufacturing the brackets, the In-Ovation C(r) ceramic model showed less friction than the metallic ones.